Objects and Other Subjects
XV, 307 p.
Keywords: The papers in this volume examine the current role of grammatical functions in transformational syntax in two ways: (i) through largely theoretical considerations of their status, and (ii) through detailed analyses for a wide variety of languages. Taken together the chapters in this volume present a comprehensive view of how transformational syntax characterizes the elusive but often useful notions of subject and object, examining how subject and object properties are distributed among various functional projections, converging sometimes in particular languages.